2020
DOI: 10.1038/s41598-020-74913-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms and fecal nucleic acid testing of children with 2019 coronavirus disease: a systematic review and meta-analysis

Abstract: In order to understand the clinical manifestations and incidence of gastrointestinal symptoms of coronavirus disease (COVID-19) in children and discuss the importance of fecal nucleic acid testing.We retrospectively analyzed studies on gastrointestinal symptoms and fecal nucleic acid detection in pediatric COVID-19 patients from January 1, 2020 to August 10, 2020, including prospective clinical studies and case reports. The results of fecal nucleic acid detection were analyzed systematically. Stata12.0 softwar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 57 publications
(33 reference statements)
1
31
0
4
Order By: Relevance
“…Moreover, in this study, it was observed that the patients admitted to intensive care units or presenting with high severity had a higher probability of abdominal pain and increased hepatic inflammatory markers (e.g., aminotransferase aspartate, alanine aminotransferase). Another study reported that, among gastrointestinal clinical manifestations, vomiting and diarrhea were more common, with a total incidence of 17.7% (95% Cl 13.9-21.5%) in pediatric patients [98]. This study also showed a rate of 85.8% (91/106) among cases that tested positive for fecal nucleic acid in children with COVID-19.…”
Section: Complications Of Gastrointestinal Hepatic and Renal Systemsupporting
confidence: 50%
“…Moreover, in this study, it was observed that the patients admitted to intensive care units or presenting with high severity had a higher probability of abdominal pain and increased hepatic inflammatory markers (e.g., aminotransferase aspartate, alanine aminotransferase). Another study reported that, among gastrointestinal clinical manifestations, vomiting and diarrhea were more common, with a total incidence of 17.7% (95% Cl 13.9-21.5%) in pediatric patients [98]. This study also showed a rate of 85.8% (91/106) among cases that tested positive for fecal nucleic acid in children with COVID-19.…”
Section: Complications Of Gastrointestinal Hepatic and Renal Systemsupporting
confidence: 50%
“…Diagnosis is usually based on the detection of viral nucleic acids in respiratory tract specimens, while faecal nucleic acid detection is often neglected. Therefore, children with gastrointestinal symptoms as the predominant manifestation of COVID-19 are often misdiagnosed[ 34 ]. Gastrointestinal manifestations are a prominent presenting feature of multisystem inflammatory syndrome in children (MIS-C).…”
Section: Epidemiology Of Covid-19 and Gastrointestinal Disorders In Childrenmentioning
confidence: 99%
“…Patients who present with gastrointestinal symptoms may have a longer duration between symptom onset and viral clearance and may have increased faecal virus positivity compared with those who present with respiratory symptoms[ 35 ]. Children have a higher nucleic acid positivity rate of faeces and prolonged faecal viral shedding compared to adults[ 34 ]. SARS-CoV-2 RNA can be found in stool specimens and anal/rectal swabs, often with more positivity than oral samples, in the late phase of the disease.…”
Section: Epidemiology Of Covid-19 and Gastrointestinal Disorders In Childrenmentioning
confidence: 99%
“…A recent systematic review showed that digestive symptoms were present in 17.7% of a total of 3028 infected pediatric patients. Vomiting, nausea, diarrhea, and anorexia were the most common gastrointestinal symptoms [ 4 ]. Another very recent systematic review with meta-analysis reported an overall prevalence of anorexia of 18%, followed by diarrhea (15%), nausea and vomiting (10%), and abdominal pain (6%) [ 5 ].…”
Section: Gastrointestinal Symptoms In Children With Sars-cov-2 Infectmentioning
confidence: 99%
“…Many pediatric COVID-19 patients have nasal obstruction, fever, runny nose, pharyngalgia, whereas signs of respiratory failure rarely occur [ 3 ]. Conversely, gastrointestinal symptoms have been demonstrated to be relatively common in pediatric COVID-19 patients [ 4 ]. Here we present a summary of: i) the current understanding of the gastrointestinal involvement in SARS-CoV-2 infected children and adolescents, and ii) the impact of COVID-19 on the clinical approach to patients with gastrointestinal disease, including diagnosis and treatment, and iii) the role and limited access to the instrumental diagnosis such as digestive endoscopy, in order to provide an overview of the clinical implications of COVID-19 for the pediatric gastroenterologist.…”
Section: Introductionmentioning
confidence: 99%